Metagenomic analysis of the bacterial community and gamma-aminobutyric acid (GABA) synthesis by lactic acid bacteria from seredele, a Balinese fermented soybean product - PURWANINGTYAS KUSUMANINGSIH; YOGA DWI JATMIKO; I GUSTI AYU KUSUMAWATI; NI WAYAN NURSINI; IDA BAGUS AGUNG YOGESWARA (Society for Indonesian Biodiversity, 2024)
Abstract. Kusumaningsih P, Jatmiko YD, Kusumawati IGA, Nursini NW, Yogeswara IBA. 2024. Metagenomic analysis of the bacterial community and gamma-aminobutyric acid (GABA) synthesis by lactic acid bacteria from seredele, a Balinese fermented soybean product. Biodiversitas 25: 4190-4198. Seredele is a fermented Balinese soybean product that undergoes spontaneous fermentation for two days at room temperature. This fermented food, commonly consumed as a condiment, has a distinctive smell similar to Japanese natto. The bacterial dynamics during fermentation using a metagenomic approach have not been reported. This study aimed to reveal bacterial dynamics during seredele fermentation and to obtain gamma-aminobutyric acid (GABA)-producing lactic acid bacteria from seredele. The bacterial dynamics of seredele were investigated using 16S rRNA sequencing. Lactic acid bacteria (LAB) were also isolated and screened for their ability to produce GABA. The metagenomics analysis showed that Weissella, Streptococcus, and Enterococcus are the most prevalent bacterial genera during fermentation. The relative abundance of bacteria at the species level indicates that W. confusa, W. paramesenteroides, E. faecium, S. lutetiensis, and E. durans are the most abundant bacteria at all stages of fermentation. Consistent with the metagenomic analysis, two strains, Limosilactobacillus fermentum A7304 and Enterococcus lactis A7303, produced 60 mg/L and 65 mg/L of GABA, respectively, in de Man Rogosa (MRS) medium enriched with 1% monosodium glutamate (MSG). This work opens opportunities to understand the bacterial dynamics in seredele and its potential as a source of GABA-producing bacteria.